Upper Basic Islamic Studies Teachers’ Perceptions of Incorporating an Inclusive System of Education in Kwara State, Nigeria - Adisa Issa Usman (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
Inclusive education has become a central focus of global educational reforms aimed at ensuring equitable learning opportunities for all learners, including those with disabilities. In Nigeria, efforts to integrate inclusive practices into basic education continue to face implementation challenges; therefore, understanding teachers’ perceptions is essential for effective policy execution. This study investigated upper basic Islamic Studies teachers’ perceptions, knowledge, and attitudes toward the incorporation of an inclusive education system in Kwara State, Nigeria. A descriptive survey design was employed, and 200 Islamic Studies teachers were selected through multi-stage, stratified, cluster, and purposive sampling techniques. Data were collected using an adapted questionnaire titled Islamic Studies Teachers’ Perceptions of Inclusive Education (ISTPIE). The instrument’s reliability was confirmed through a test–retest procedure, yielding a coefficient of 0.86. Descriptive statistics (percentage, mean, and standard deviation) were used to answer the research questions, while independent t-test and ANOVA were applied to test the hypotheses at the 0.05 significance level. Findings indicated that teachers exhibited moderate levels of perception, knowledge, and attitude toward inclusive education. Results further showed no significant differences in teachers’ perceptions based on gender or educational qualification. The study concludes that although Islamic Studies teachers possess basic awareness of inclusive education, concerns persist regarding its feasibility due to systemic constraints. This research contributes empirical evidence to support policy dialogue on teacher preparedness and highlights the need for targeted professional development to enhance teachers’ capacity for effective, inclusive classroom practices.